Association between polymorphisms in catechol-O-methyltransferase (COMT) and cocaine-induced paranoia in European-American and African-American populations - Ittiwut, Rungnapa (2011)
Catechol-O-methyltransferase (genetic locus, COMT) is a major enzyme involved in catecholamine metabolism and has been associated with numerous psychiatric phenotypes. We studied COMT SNPs and haplotypes in cocaine-induced paranoia (CIP) in African-American (AA) and European-American (EA) populations. We genotyped 17 SNPs across the COMT locus in 319 AA pedigrees (848 individuals) and 302 EA pedigrees (707 individuals). Family-controlled association analyses were conducted using FBAT. We found SNP rs737865 to be nominally significantly associated in the AA family population (p=0.05). In EAs, the best-known marker, rs4680 (Val158Met), was nominally significant in additive models (p=0.03). SNP rs174696 also showed nominal significance in additive models (p=0.02). We considered the 3 SNPs (rs737866-rs4680-rs174696) together in haplotype analysis in both family populations, using HBAT. The A-A-T haplotype was significantly associated with CIP in EAs (Z=2.845; p=0.0044, global p=0.020). We then studied COMT SNPs in an additional 738 AA and 404 EA unrelated cocaine dependent individuals with and without paranoia. The A-A-T haplotype was significantly associated to CIP in the AA unrelated population (p=0.0015). Two haplotypes, A-G-C and A-A-C, were significant in the EA unrelated population (p=0.001 and p=0.0003). We also identified rs4680 and three other SNPs, rs933271, rs5993883, and rs740603, as potentially functional variants, as predicted by a signature of positive selection in unrelated EAs and AAs. Based on our robust family-controlled and unrelated-affected analyses, we conclude that COMT is associated with CIP, possibly as a result of its role in the metabolism of dopamine and norepinephrine.